Informatization of trade education of future teacher of physical culture - Dragnev Y.V (Kharkov National Pedagogical University, 2012)
Resolved, that the informatization of professional education of future teachers of physical culture is one of the most important components of the restructuring of the system of physical education; the defining element of the information society on the basis of introduction of modern information technologies. Is shown, that for successful solution of the problems of informatization of professional education of future teachers of physical culture appropriate to comprehensively carry out research on the formation of computer literacy, information competence, information culture in the branch of knowledge "Physical education, sport and health".